BENTUK DAN FUNGSI KESENIAN TIBAN DI DESA WAJAK KECAMATAN BOYOLANGU KABUPATEN TULUNGAGUNG - Dera Vernanda Willya Putri; Sriyadi Sriyadi (Institut Seni Indonesia Surakarta, 2021)
This research aims to address two problems related to the dance form dan the function of Tiban, including : (1) how the dance form of Tiban in Wajak Village Boyolangu District Tulungagung Regency , (2) how the function of Tiban in society people who lived in Wajak Village Boyolangu District Tulungagung Regency. These two problems are analyzed based by theory dance form from Soedarsono and theory of function from Bronislaw Malinowski , Anthony Shay, and Sumandiyo Hadi. This research is qualitative methods. Qualitative teqnique of data is triangulation data that include of observation, interviews, ad bibliographical study. The results of this research refers that dance form and the function of Tiban. The dance form include of the structure of performance and the elements of dish. The performance of Tiban have many function that influent by the society lived of people in Wajak Village Boyolangu District Tulungagung Regency. Dance as an existention of self, dance as a ritualsm, dance as reflection activity and streght of society, Dance show of aesthetic, and dance as economy system.